Step
*
1
1
1
of Lemma
free-1-normal-form
1. [S] : Type
2. ∀x,y:S.  (x = y ∈ S)
3. s : S
4. x : Point(free-vs(ℤ-rng;S))
5. (λx.Σ(p∈x). let k,s = p in k) = (λx.Σ(p∈x). let k,s = p in k) ∈ free-vs(ℤ-rng;S) ⟶ ℤ
6. (λk.{<k, s>}) = (λk.{<k, s>}) ∈ ℤ ⟶ free-vs(ℤ-rng;S)
7. (λb.Ax) = (λb.Ax) ∈ (∀a:Point(free-vs(ℤ-rng;S)). ({<Σ(p∈a). let k,s = p in k, s>} = a ∈ Point(free-vs(ℤ-rng;S))))
8. λa.Ax ∈ ∀b:Point(ℤ). (Σ(p∈{<b, s>}). let k,s = p in k = b ∈ Point(ℤ))
⊢ ∃k:ℤ. (x = {<k, s>} ∈ Point(free-vs(ℤ-rng;S)))
BY
{ All (Fold `member`) }
1
1. [S] : Type
2. ∀x,y:S.  (x = y ∈ S)
3. s : S
4. x : Point(free-vs(ℤ-rng;S))
5. λx.Σ(p∈x). let k,s = p 
              in k ∈ free-vs(ℤ-rng;S) ⟶ ℤ
6. λk.{<k, s>} ∈ ℤ ⟶ free-vs(ℤ-rng;S)
7. λb.Ax ∈ ∀a:Point(free-vs(ℤ-rng;S)). ({<Σ(p∈a). let k,s = p in k, s>} = a ∈ Point(free-vs(ℤ-rng;S)))
8. λa.Ax ∈ ∀b:Point(ℤ). (Σ(p∈{<b, s>}). let k,s = p in k = b ∈ Point(ℤ))
⊢ ∃k:ℤ. (x = {<k, s>} ∈ Point(free-vs(ℤ-rng;S)))
Latex:
Latex:
1.  [S]  :  Type
2.  \mforall{}x,y:S.    (x  =  y)
3.  s  :  S
4.  x  :  Point(free-vs(\mBbbZ{}-rng;S))
5.  (\mlambda{}x.\mSigma{}(p\mmember{}x).  let  k,s  =  p  in  k)  =  (\mlambda{}x.\mSigma{}(p\mmember{}x).  let  k,s  =  p  in  k)
6.  (\mlambda{}k.\{<k,  s>\})  =  (\mlambda{}k.\{<k,  s>\})
7.  (\mlambda{}b.Ax)  =  (\mlambda{}b.Ax)
8.  \mlambda{}a.Ax  \mmember{}  \mforall{}b:Point(\mBbbZ{}).  (\mSigma{}(p\mmember{}\{<b,  s>\}).  let  k,s  =  p  in  k  =  b)
\mvdash{}  \mexists{}k:\mBbbZ{}.  (x  =  \{<k,  s>\})
By
Latex:
All  (Fold  `member`)
Home
Index